Barriers to Care in Veterinary Services: Lessons Learned From Low-Income Pet Guardians' Experiences at Private Clinics and Hospitals During COVID-19 - Morris, Amy; Wu, Haorui; Morales, Celeste (Frontiers in Veterinary Science, 2021)
This qualitative study aimed to explore the experiences of low-income pet guardians in accessing veterinary care during COVID-19. Participants were recruited through a purposive sampling method: 12 individuals who applied to and met the low-income threshold to access support for veterinary fees from the Vancouver Humane Society (VHS) were invited for semi-structured in-depth telephone interviews. Participants indicated that they experienced pandemic-related barriers related to and compounded by their low-income status. Their experiences fit into three categories: the barriers to accessing veterinary care pre-and peri-COVID-19, the emotional impact of compounding barriers related to accessing veterinary care during COVID-19, and the human-animal bond and resilience in the context of COVID-19. Drawing on the One Health, One Welfare approach, we argue that veterinary and animal services should evaluate and improve their support services, particularly programs developed for low-income pet guardians. Based on the participants’ recommendations, we propose that veterinary and animal services prepare for future disaster situations by increasing their financial capacity to support people needing assistance, undergoing training to better work with people experiencing financial and emotional stress, and providing easily accessible resources to better distribute knowledge about animal needs and available financial assistance programming. The suggestions are intended to benefit animals, their guardians, and both veterinary and animal service sector workers.